The barefoot architect a handbook for green building - Lengen, Johan van (Shelter Publications, 2008)
"A fully comprehensive guide to building in the tropical world, 'Barefoot Architect' covers everything from how to build in various climates, to the step-by-step practicalities of building homes that suit the local environment."